Synergistic Strengthening by Severe Plastic Deformation and Post‐Heat Treatment of a Low‐Carbon Steel. Issue 6 (8th March 2018) - Soleimani, Foad; Kazeminezhad, Mohsen
Abstract : Low‐carbon steel sheets are severely plastic deformed to strains of up to ≈3.48 and subsequently heat treated by conventional annealing followed by water‐quenching. Four temperatures are chosen for the annealing below and over the A c1 and A c3 transformation lines. The effects of post‐deformation heat treatment are investigated by evaluating the microstructure and mechanical properties, including strength, ductility, work hardening capability, and hardness. A maximum increase of 86% in the strength is obtained through intercritical annealing and quenching of the samples subjected to strain of 1.16. It is interesting that both the elongation and ultimate tensile strength values are higher after heat treatment at a variety of temperatures in comparison with those of the non‐treated samples; up to 197% for the former and up to 33% for the latter. These would be achieved in combination with yield ratios even lower than that of the as‐received material, demonstrating the higher deformation capability of the specimens. However, these beneficial outcomes are deteriorated toward higher amounts of strain. Despite the heat treated undeformed low‐carbon steels, the stress − strain curves for heat treated deformed samples show little or no discontinuous yielding correlated to variations of mobile dislocations density as a result of microstructural evolution. Abstract : Although there are scattered reports on heat treatment of SPDed low‐carbon steels, it is the first time that effects of annealing at various temperatures and subsequent quenching on such steels are comprehensively studied. Heat treatment of deformed specimens can notably increase both the strength and ductility, together with deformation capabilities even higher than raw sample and elimination of Lüders bands.